GAMBARAN FAAL PARU DAN SKORING ASTHMA CONTROL TEST (ACT) PENDERITA ASMA RAWAT JALAN DI POLIKLINIK PARU RSUD ARIFIN ACHMAD PEKANBARU - Setiahasti Saily Saily; Adrianison "; Eka Bebasari Bebasari (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Asthma is a chronic inflammatory disorder of the airways. Spirometry is an examination technique to assessment lung function of patient asthma and Asthma Control Test (ACT) as a tool consist of questionaires to assessing controlled asthma, ACT are subjective but has been validated and can be used easily. This research aimed to determine description of lung function and scoring Asthma Control Test (ACT) in pulmonologic outpatient clinic general hospital Arifin Achmad Pekanbaru. Design of the study was descriptive cross sectional and accidental sampling method already done January until March 2014 accordance to the inclusive criteria. Amount of samples are 73 asthma patients were asked to fill out questionaires of ACT under the supervision of researchers and asthma patient following spirometry screening. The result of this research is asthma patient characteristics more in age group between 45-54 years (39,73%), gender more in woman (78,08%), status of nutrient more in normal weight (32,51%), more work as housewife (46,58%), smoking history more as former smoker (43,75%), and more in classified as moderate persistence asthma (47,94%). Asthma control more were controlled (57,53%), more pulmonary faal were mild obstructive (52,05%), and comparison of pulmonary faal and ACT there are (30,14%) more in obstructive classified with controlled asthma.Key words : Asthma patient, spirometry, Asthma Control Test (ACT)